A tecnificação do território no Cariri paraibano associada às políticas de estímulo a (re)pecuarização e a prática do cooperativismo agropecuário - Rêgo, Eduardo Ernesto do (2019)
The mechanization of the field promoted in the last decades has caused significant transformations in the technical bases of the Brazilian rural territory, triggering, among other factors, the technification of agricultural infrastructure and the modernization of dairy farming in the northeastern semi-arid region. In the midst of this process, we also found an expressive territorial configuration and a new rationality in certain portions of the territory of Paraíba, especially in the Cariri region. In this sense, the main objective of this thesis was to understand the process of technification of the territory in the Cariri region of Paraíba, based on the stimuli generated by the public policies to encourage re - stocking and the practice of cooperativism and agricultural associations. From the theoretical point of view, the research established an interlocution between the authors that are dedicated to the discussion of the concepts of: technification, (re)pecuarization, public policies, associativism and cooperativism. Thus, we present in the paper the role of the State in the process of technification of the Brazilian territory from the implementation of public policies of rural development, where we had as temporal cuts the 1950s with the beginning of conservative modernization in the countryside, and the decade of 1990 with the implementation of public policies and actions to stimulate (re) cattle raising in the northeastern semi-arid region. In the body of the research, we also highlight the importance of cooperativism and associativism for the modernization of dairy farming, and for the technification of the territory in the study. In the documentary phase of the research, we conducted data collection, considering two perspectives: secondary data related to the municipalities that make up the study area and primary data obtained directly from cooperatives and associations, the Municipal Secretariats of Agriculture and Rural Development and the Assistance Company Technique and Rural Extension (EMATER). Secondary source data were collected from the Agricultural Census and the Aggregated Data Bank, both from the Brazilian Institute of Geography and Statistics (IBGE), in order to broaden the knowledge and information on agricultural production and the mechanization found in the municipalities surveyed. In the fieldwork stage, we conducted interviews with rural producers and applied questionnaires to cooperatives and agricultural associations located in the municipalities selected to carry out the activity. From the quantification and analysis of the primary and secondary data collected, we established the technification pattern of the territory of the municipalities chosen to compose the field work, which enabled us to identify in a hierarchical way, the technification points arranged in the Cariri territory of Paraíba, expressed through the modernization of dairy farming.